2020
DOI: 10.1002/chem.201905446
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic Bifunctional trans‐Cyclooctenes as Efficient Tools for Investigating Click‐to‐Release Kinetics

Abstract: The inverse electron demand Diels-Alder pyridazine elimination reactionb etween tetrazines and allylic substituted trans-cyclooctenes (TCOs) is ak ey player in bioorthogonal bond cleavage reactions. Determining the rate of eliminationo fa lkylamine substrates has so far provend iffi-cult. Here, we report af luorogenic tool consisting of aT COlinked EDANS fluorophore and aD ABCYL quencher for accurate determination of both the click and releaser ate constants for any tetrazine at physiologically relevant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…These data suggest that elimination of the TCO-cage occurs negligibly fast in human cells. Typical ligation kinetics are on the order of 10 3 M –1 s –1 , and consequent elimination can proceed with a reaction constant of 0.06 s –1 ( t 1/2 = 13 s) at physiological pH. , It should be noted that full recovery of agonist is likely not required for the induction of TLR2 signaling, meaning that the kinetics of NF-κB nuclear translocation may not accurately reflect the true uncaging kinetics. Still, the data illustrate the power of the Tz-induced “click-to-release” reaction for triggering the near-instantaneous activation of TLR2 in cells pretreated with TCO-P 2 TEG, making this (un)­caging strategy extremely powerful for precisely controlling TLR2 activation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that elimination of the TCO-cage occurs negligibly fast in human cells. Typical ligation kinetics are on the order of 10 3 M –1 s –1 , and consequent elimination can proceed with a reaction constant of 0.06 s –1 ( t 1/2 = 13 s) at physiological pH. , It should be noted that full recovery of agonist is likely not required for the induction of TLR2 signaling, meaning that the kinetics of NF-κB nuclear translocation may not accurately reflect the true uncaging kinetics. Still, the data illustrate the power of the Tz-induced “click-to-release” reaction for triggering the near-instantaneous activation of TLR2 in cells pretreated with TCO-P 2 TEG, making this (un)­caging strategy extremely powerful for precisely controlling TLR2 activation.…”
Section: Resultsmentioning
confidence: 99%
“…33,34,36,38 The speed of the reaction drives TCO-elimination in an almost instantaneous "switch-like" manner, which is of crucial importance when investigating the complex kinetics of receptor signaling. 31,32 Here, we set out to develop a C2R-approach for conditionally controlling the activation of TLRs. We focused on TLR2 (Figure 1), because many of its downstream signaling properties remain to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… [17] The authors reported the formation of a mixture of the axial and equatorial difunctionalized TCO derivatives after isomerization with UV‐light and a sensitizer as described by the Fox group (Figure 1B). [25] Currently, the synthetic accessibility of the most commonly used difunctionalized TCOs with releasing properties is rather problematic, mainly due to low yielding steps and a lengthy overall synthesis [17,24] . Ideally, a TCO should have multiple orthogonal handles, a fast click reaction with a tetrazine and a rapid release functionality.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Currently, the synthetic accessibility of the most commonly used difunctionalized TCOs with releasing properties is rather problematic, mainly due to low yielding steps and a lengthy overall synthesis. [16,23] Ideally, a TCO should have multiple orthogonal handles, a fast click reaction with a tetrazine and a rapid release functionality. In comparison with the difunctionalized TCO of Rossin et al, a shorter and higher yielding synthesis method of a TCO with similar properties is desired.…”
Section: Introductionmentioning
confidence: 99%